Strengthening Pentahelix Actors’ Literacy in Sustainable Tourism Development in Central Aceh Regency - Ramdansyah Fitrah; Hilliyani Hilliyani; Abidah Abidah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The development of sustainable tourism requires effective cross-sector collaboration through a pentahelix approach that engages government, academia, business, community, and media stakeholders. However, the low literacy of pentahelix actors, meaning their understanding of sustainable tourism concepts and practices, often hinders the realization of sustainable tourism, especially in areas with natural and cultural tourism potential, such as Central Aceh Regency. This community service activity aims to strengthen the literacy of Pentahelix actors in sustainable tourism development through a Community-Based Participatory Research (CBPR) approach. The implementation methods include mapping initial literacy conditions, participatory identification of needs, designing a collaborative literacy program, implementing training and discussions, and evaluating and formulating sustainability recommendations. The outputs of the activity include increased literacy among pentahelix actors, as reflected in changes in their level of understanding (pre-post), increased participation and collaborative commitment, the development of contextual literacy programs, and recommendations for the sustainable development of regional tourism. The impact of the activity demonstrates strengthened capacity among pentahelix actors, the formation of a cross-sector dialogue space, and increased awareness of the importance of integrating sustainability principles into tourism practices and policies. This activity confirms that strengthening participation-based literacy is a strategic foundation in promoting pentahelix collaboration and sustainable tourism development in Central Aceh Regency.